Two shades of opacity: Hidden orders and dark trading - Degryse, Hans; Karagiannis, Nikolaos; Tombeur, Geoffrey; Wuyts, Gunther (Journal of Financial Intermediation, 2021)
Regulators are concerned that large volumes of trading outside lit venues (i.e., dark trading) harms the functioning of financial markets. In contrast, regulators are neutral about hidden-order trading as these occur on lit venues and are associated with positive effects on market quality. An unanswered economic question concerns the interrelation between these two types of opaque trading, i.e., hidden orders and dark trading. Employing two different empirical methodologies we find that dark and hidden-order trading are substitutes. We also show that both types of opaque trading increase when markets are volatile and fewer algorithmic trading occurs. Smart order routing increases dark trading but reduces hidden-order activity.